A Multiprobe Heat Pulse Sensor for Soil Moisture Measurement Based on PCB Technology - Morais Franca, Maria Bernadete de; Morais, Flavio J. O. [UNESP]; Carvalhaes-Dias, Pedro; Duarte, Luis Caparroz; Siqueira Dias, Jose A. (Ieee-inst Electrical Electronics Engineers Inc, 2019)
Heat dissipation sensors operate based on the temperature dependence of the transient heat conduction within the soil, which is a function of the soil characteristics and its water content. After a heat pulse with controlled energy is applied to a heater, it is possible to show that the maximum temperature rise Delta T-M measured in the temperature sensing element can be related to the volumetric water content of the soil theta(v) [m(3) m(-3)]. The design and fabrication of a low-cost soil moisture multiprobe heat pulse sensor system using conventional printed circuit boards and surface-mount devices is presented. The proposed sensor is free of the needles' deflection problem present in conventional multiprobe sensors and is manufactured using conventional off-the-shelf electronic components. A precision low-power electronic signal conditioning circuit, using an instrumentation switched-capacitor building block, was developed and successfully used in the prototype. Due to an energy-efficient topology for the sensor and a low-power signal conditioning circuit, the average current consumption of the system (with one measurement per day) is only 3 mu A. To demonstrate the feasibility of the concept, a prototype of the sensor was tested in soils with volumetric humidity in the range from theta(v) = 0.05 m(3) m(-3) to theta(v) = 0.41 m(3) m(-3) and, with a very low heating energy pulse (3 J), showed a sensitivity, normalized by the total energy applied, Gamma = 211 x 10(-3) degrees C m(3) m(-3) J(-1). Compared with a button heat pulse probe sensor which has Gamma = 192 x 10(-3) degrees C m(3) m(-3) J(-1), the developed sensor shows a higher normalized sensitivity.
Keywords: Heat pulse sensors; low-power circuits; multi-probe sensors; printed circuit board (PCB) technology; signal conditioning circuit; soil moisture sensors